MOBILE PHONE BRANDS PREFERENCES AMONG STUDENTS: COMPARATIVE STUDIES IN INDONESIA AND MALAYSIA - Silvia Dewi Sagita Andik; Jono Munandar; Mukhamad Najib; Abdul Rashid (School of Business, IPB University (SB-IPB), 2021)
In recent years, various brands of mobile phones have dominated Indonesia and Malaysia market. Most of them are imported from other countries, such as China, America, Europe, and South Korea which are highly competitive by offering the variety of designs and functions. To compete with other competitors, Indonesian telecommunication industry needs to focus on brand management, especially in building brand preference. The aims of this research to examine factors affecting brand preference. Questionnaire surveys have been conducted to 200 respondents in Indonesia & Malaysia. Data were analyzed by descriptive and Structural Equation Modeling Partial Least Square (SEM-PLS). SEM PLS has been conducted in order to examine the relative impact of the identified factors on brand preference. The major findings are there were differences factors affecting brand preference of mobile phone between Indonesian consumers and Malaysian consumers. Indonesian consumers are more focused on brand awareness when they have to choose mobile phone brands. On the other hands, Malaysian consumers are more focused on brand experience. Keywords: brand awareness, brand experience, brand preference, mobile phone brand, structural equation modeling